Lymphokine-mediated regulation of the proliferative response of clones of T helper 1 and T helper 2 cells (The Rockefeller University Press, 1988)
Murine Th1 and Th2 subsets differ not only in the lymphokines they produce, but also functionally. It is not clear what factors influence the preferential activation of one subset versus the other and what regulatory interactions exist between them. The purpose of this study was to examine the effect of lymphokines produced by clones of Th1 cells (IL-2 and IFN-gamma), Th2 cells (IL-4), and APC (IL-1) on the proliferative response of Th1 and Th2 cells after antigenic stimulation. Activation of both types of clones in the presence of antigen and APC resulted in the acquisition of responsiveness to the proliferative effects of both IL-2 and IL-4, although Th2 cells were more responsive to IL-4 than Th1 cells. Responsiveness of Th1 and Th2 cells to both lymphokines decreased with time after initial antigenic activation; Th1 cells lost their responsiveness to IL-4 more rapidly and to IL-2 more slowly than Th2 cells. IFN-gamma partially inhibited the IL-2 and IL-4-mediated proliferation of Th2, but not Th1 cells. Although the presence of IL-1 was not required for the response of Th1 or Th2 cells to IL-4, its presence resulted in a synergistic effect with IL-2 or IL-4 in Th2 but not in Th1 cells. Both subsets responded to a mixture of IL-2 and IL-4 in synergistic fashion. Delayed addition and wash-out experiments indicated that both IL-2 and IL-4 had to be present simultaneously in order for synergy to occur. These results suggest that Th cell subsets might regulate each other via the lymphokines that they secrete and that the pathways of IL-2 and IL-4 mediated proliferation are interrelated.